Pengaruh Vegetasi dalam Mengurangi Tingkat Kebisingan Lalu Lintas pada Kawasan Perdagangan di Kec. Nanggalo, Kota Padang (Studi Kasus: SJS Plaza Padang dan Pasar Nanggalo) - Chandra, Deded; Irwansyah, Arief (Al-DYAS, 2025)
This study aims to: (1) Determine the level of traffic noise in the commercial areas of SJS Plaza Padang and Pasar Nanggalo. (2) Assess the impact of vegetation in reducing traffic noise levels. This research employs a descriptive quantitative approach. The population in this study consists of commercial areas in Nanggalo District, Padang City, where vegetation is available as the research object. The sample includes two different commercial locations: SJS Plaza Padang and Pasar Nanggalo. Data collection was conducted at two points in each location (in front of the vegetation and behind the vegetation), resulting in four measurement points in total. The research finding: (1) Traffic Noise Levels: The noise level in the SJS Plaza Padang commercial area ranges between 81.1 dB – 87.3 dB. The lowest noise level at SJS Plaza Padang is 81.1 dB, occurring on a holiday morning, while the highest noise level is 87.3 dB, occurring on a holiday afternoon. The noise level in the Pasar Nanggalo commercial area ranges between 73 dB – 80.1 dB. The lowest noise level at Pasar Nanggalo is 73 dB, occurring on a holiday afternoon, while the highest noise level is 80.1 dB, occurring on a weekday morning. (2) Effect of Vegetation on Noise Reduction The regression test results indicate a small effect of vegetation on noise reduction, with a coefficient of -0.001 between leaf canopy volume and traffic noise reduction. This means that every 1 m³ increase in leaf canopy volume only reduces noise levels by 0.001 dB. Therefore, combining vegetation with barriers such as concrete walls or sound fences, along with strategic urban design, can provide a more effective and sustainable solution for reducing traffic noise in larger areas.